A laser-plasma accelerator driven by two-color relativistic femtosecond laser pulses - Li Song; Li Guangyu; Ain Quratul; Hur Min Sup; Ting Antonio C.; Kulagin Victor V.; Kamperidis Christos; Hafiz Nasr Abdelrahman Mohamed (2019)
A typical laser-plasma accelerator (LPA) is driven by a single, ultrarelativistic laser pulse from terawatt- or petawatt-class lasers. Recently, there has been some theoretical work on the use of copropagating two-color laser pulses (CTLP) for LPA research. Here, we demonstrate the first LPA driven by CTLP where we observed substantial electron energy enhancements. Those results have been further confirmed in a practical application, where the electrons are used in a bremsstrahlung-based positron generation configuration, which led to a considerable boost in the positron energy as well. Numerical simulations suggest that the trailing second harmonic relativistic laser pulse is capable of sustaining the acceleration structure for much longer distances after the preceding fundamental pulse is depleted in the plasma. Therefore, our work confirms the merits of driving LPAs by two-color pulses and paves the way toward a downsizing of LPAs, making their potential applications in science and technology extremely attractive and affordable.
Keywords: Fizikai tudományok